2018
DOI: 10.1038/s41598-018-20610-y
|View full text |Cite
|
Sign up to set email alerts
|

Dlgap1 knockout mice exhibit alterations of the postsynaptic density and selective reductions in sociability

Abstract: The scaffold protein DLGAP1 is localized at the post-synaptic density (PSD) of glutamatergic neurons and is a component of supramolecular protein complexes organized by PSD95. Gain-of-function variants of DLGAP1 have been associated with obsessive-compulsive disorder (OCD), while haploinsufficient variants have been linked to autism spectrum disorder (ASD) and schizophrenia in human genetic studies. We tested male and female Dlgap1 wild type (WT), heterozygous (HT), and knockout (KO) mice in a battery of behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 82 publications
2
31
0
Order By: Relevance
“…Several of these interactions have been previously observed to modulate neuronal function in model systems. For example, SHANK3 interacts with DLG1 through the mediator protein DLGAP1 to influence post-synaptic density in mice [66] and binds to proteins in the Rac1 complex, including PAK2, to regulate synaptic structure [67,68]. These results suggest that homologs of 3q29 genes interact with key developmental genes in conserved pathways to modify cellular phenotypes.…”
Section: Homologs Of 3q29 Genes Interact With Canonical Neurodevelopmmentioning
confidence: 98%
“…Several of these interactions have been previously observed to modulate neuronal function in model systems. For example, SHANK3 interacts with DLG1 through the mediator protein DLGAP1 to influence post-synaptic density in mice [66] and binds to proteins in the Rac1 complex, including PAK2, to regulate synaptic structure [67,68]. These results suggest that homologs of 3q29 genes interact with key developmental genes in conserved pathways to modify cellular phenotypes.…”
Section: Homologs Of 3q29 Genes Interact With Canonical Neurodevelopmmentioning
confidence: 98%
“…DLG associated protein 1 (DLGAP1), also known as Disks large-associated protein 1 (DAP-1), guanylate kinase-associated protein (GKAP), localizes at the postsynaptic density (PSD). DLGAP1 knockout mice exhibited alterations of the postsynaptic density and selective reductions in sociability (16). Additionally, previous literatures showed that DLGAP1 is mainly involved in the neuropsychiatric disorders, such as autism spectrum disorder (ASD), obsessive-compulsive disorder (OCD) and schizophrenia (SCZ).…”
Section: Discussionmentioning
confidence: 99%
“…Post-synaptic density proteins (PSD) play a critical role in regulating the density and activity of glutamate receptors. As a scaffold protein localized at the PSD of glutamatergic neurons, Dlgap1 knockout leads to disruption of protein interactions in the PSD, and de cits in sociability [38]. And, TANC1 is a PSD-95-interacting synaptic protein that contains multiple domains for protein-protein interactions, important for dendritic spine maintenance and spatial memory [39].…”
Section: Discussionmentioning
confidence: 99%